Angelo Paredi, S. Ambrogio e la sua età. Milano, Vlrico Hoepli, 1994, 565 pp. - Hubeñak, Florencio (1995)
Fil: Hubeñak, Florencio. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina